The live pig supply chain as reported by farmers in selected districts affected by African swine fever in Uganda, June and July 2022 - Nawatti, Margaret; Ekakoro, John E.; Singler, David; Ochoa, Krista; Kizza, Robinah; Ndoboli, Dickson; Ndumu, Deo B.; Wampande, Eddie M.; Havas, Karyn A. (Frontiers in Veterinary Science, 2023)
Introduction: Uganda is a pork-producing country in East Africa. The African swine fever virus (ASFV) has had a devastating impact on the country’s pig industry. The movements of pigs and pork are a major pathway of spreading ASFV. This study was done to describe the live pig supply chain within and through districts that are impacted by African swine fever (ASF) in Uganda. Methods: A pig farmer survey in districts known to have ASFV was done using a semi-structured questionnaire available in English and two local languages. In total, 99 farmers were interviewed across five districts. Farmers were conveniently and purposively selected by local government veterinary officials. An online key informant survey was also used to validate farmer responses. Results: Most farmers interviewed in all districts reported to source and sell most of their pigs from within their district the farm was in, although there was variation by district and pig type. In relation to pig type, 89.7% of farmers sourced sows, 80.0% sourced boars, and 96.4% sourced weaned pigs from the district where the farm was located. As for sales, 91.3% of farmers sold sows, 92.7% sold boars, 91.9% sold weaned pigs, and 92.2% sold market pigs in the district where the farm was located. There was also variation to whom pigs were sold and sourced by pig type. Conclusions: This information is useful when planning the scale and focus of disease control programs based on animal movement. This study revealed that pig disease control programs can be targeted to smaller regions. Furthermore, there is a need for farmers and pig traders to be educated on and adhere to veterinary regulations of animal movement and good biosecurity practices to reduce disease spread when purchasing and selling pigs from known ASFV infected areas.